Dynamic analysis of ISD suspension based on mechanical impedance. (September 2020) - Xu, Long; Chen, Yijie; Du, Fu; Zhang, Zichao; Wang, Le
Abstract: The development of inerter has brought rapid development of vehicle suspension's configuration design. More and more inerter vibration isolation networks have been proposed by scholars. As vibration isolation networks became more complex, traditional dynamic model calculations became difficult. So, a mechanical impedance dynamic model was proposed in this paper, which can be applied to the suspension of different vibration isolation networks. At the same time, the influence of the inerter on the frequency of the three-element parallel ISD suspension was studied, which provides a basis for the selection of suspension parameters.